Socio-environmental indicators of Aedes aegypti breeding sites in the southern extremity of Santa Catarina state - Ivan Merêncio (Acta Brasiliensis, 2018)
This research analyzed the spatial distribution of Aedes aegypti breeding sites found in 2016 in the fifteen cities of the Municipalities Association of the Extreme South of Santa Catarina (AMESC). These data were compared with socioenvironmental indicators (rainfall, temperature, basic sanitation and population). All data are secondary, available by different government agencies. A total of 44 mosquitoes breeding sites were observed throughout 6 cities, and the Passos de Torres city concentrated 61% of them. This city has a frontier with Rio Grande do Sul State, an affected region, and it is crossed longitudinally by the BR-101 highway, as well as other cities with a high rate of infestation. This may indicate that BR-101 is the main means of vector dispersion.  A higher occurrence vector in the warmer seasons (summer and autumn) was observed, there was no correlation to precipitation, although it rained more in 2016 than the historical average to the study area. Despite the good coverage of the water supply, there is no data about solid waste for the cities most affected, nor about the sanitary sewage in the region. So, the unavailability of specific data on sanitation impaired a detailed analysis about this indicator. This information can be used by public managers for the definition of Aedes aegypti control guidelines, but more complementarities are needed at the local level.